Degradation Profiles of Non-lignin Constituents of Corn Stover from Dilute Sulfuric Acid Pretreatment. (3rd May 2016) - Jiang, Faxian; Zhou, Xin; Xu, Yong; Zhu, Junjun; Yu, Shiyuan
Abstract : Corn stover was separated into four derived streams: ethanol extractives (EE), hot water extractives (HWE), extracted cellulose, and extracted hemicelluloses. They were separately treated with 0.75% dilute sulfuric acid at 180°C for 40 minutes. Over 100 degradation products were separated and identified using gas chromatography-mass spectrometry (GC-MS) and liquid chromatography (LC). These products contained compounds from several chemical classes, including sugars, aromatics, carboxylic acids, furans, alcohols, aldehydes, and cyclenes. Itaconic acid, succinic acid, fumaric acid, azelaic acid, DL-isoborneol, and 3-methyl-2-furoic acid were detected in the dilute sulfuric acid pretreated corn stover for the first time. Potential microbial fermentation inhibitors and valuable chemical building blocks were evaluated. In an effort to identify and develop inhibitors which are useful for controlling and improving the lignocellulosic biorefinery process, how they originated from the corn stover constituents was examined.